Song sung true: performing the nation. - Subramanian, Lakshmi (South Asian History & Culture, 2018)
This article examines the public life of Indian classical music before and after independence. It grounds the articulation of a classical music tradition - style and repertoire - within the nationalist cultural project and identifies important changes in the project after independence. These changes were largely tied to the assertion of regional identities and aspirations that occasionally disrupted the dominant nationalist imagination but by and large conformed to the same. This article tracks the formation of the nationalist cultural project spearheaded by new elites in colonial cities for whom the preservation and redefinition of the classical arts became a matter of serious investment. Music and performance formed an integral element in this as a result of which music appreciation societies came into being and grappled with the challenges of relocating traditional music practices associated with courts and salons in a new public setting. The process of relocation was tied up with the assemblage of new icons intended for performing the nation, a task that the independent Indian state continued with through its new mediums of information and communication.